Partnerships and the Sustainable Development Goals - Murphy, Enda.; Banerjee, Aparajita; Walsh, Patrick Paul. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This volume fills a significant gap in the scientific and policy literature on the Sustainable Development Goals (SDGs) and on SDG 17 which focuses on partnership as a means of implementation (MOI) for the SDGs. The collection offers a strong theoretical context, and outlines the nature of partnerships (e.g. alternative forms, multi-level forms, barriers to take-up) using the most recent UN database as well as through key case studies that highlight partnership successes and failures at local, national and global scales. The text covers a brief history and background of partnerships and the SDGs, an analysis of existing SDG partnership using UN data, a scalar analysis of case studies involving multi-stakeholder partnerships, and recommendations for successful partnership models and implementation strategies. The book will be relevant for a wide variety of readerships including academics in different policy fields and disciplines, policymakers, SDG advocates and practitioners, and NGOs active in the promotion of the SDGs and environmental issues. .
Chapter 1-The UN Sustainable Development goals -- Chapter 2-Partnerships and SDG Implementation -- Chapter 3-SDG Governance and Partnership -- Chapter 4-Partnering for data harvesting, sharing and analysis: the UN open SDG data hub -- Chapter 5-Modelling and Assessing Multi-Stakeholder Relationships: The Case of Collaboration in Global Public-Private Partnerships -- Chapter 6-National Partnerships for the Sustainable Development Goals: Multi-stakeholder partnerships in Ireland -- Chapter 7-Comparing practical SDG partnerships in Wales and Sweden -- Chapter 8-Learnings and reflections from Sustainable Antioquia: A Colombian pioneer experience of SDG -- Chapter 9-Mapping an Ecosystem of Minnesota Organizations and Corporations in Alignment to the Sustainable Development Goals -- Chapter 10-Ingredients for Partnership Success and Failure -- Chapter 11-Conclusions and Recommendation.
Keywords: Environmental sciences-Social aspects; Economic geography; Economic development; Environmental Social Sciences; Economic Geography; Development Studies